PENGARUH LINGKUNGAN KERJA FISIK DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT DUA BAROKAH SEJAHTERA (D'BRO CHICKEN & BURGER) KOTA DEPOK - Nurlaili Rahmah; Agrasadya (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of the physical work environment and motivation on employee performance at PT. Dua Barokah Sejahtera (D'BRO Chicken & Burger) Depok City. The method used is quantitative. The sample collection technique used saturated samples and a sample of 56 respondents was obtained. The method used to test and analyze the influence partially and simultaneously is by using hypothesis testing (t test and f test). Based on the research results of Hypothesis Testing (t Test) for the Physical Work Environment variable (X1) on Employee Performance (Y), the calculated t value > t table or (9.661 > 1.674) was obtained. This is reinforced by a significance value < 0.050 or (0.001 < 0.050). Thus, H01 is rejected and Ha1 is accepted, this shows that there is a significant influence between the physical work environment on employee performance. Hypothesis Test Results (t Test) Motivational Variables (X2) on Employee Performance (Y) Based on the research results, the calculated t value > t table or (8.851 > 1.674) was obtained. This is reinforced by significance value < 0.050 or (0.001 < 0.050). Thus, H02 is rejected and Ha2 is accepted, this shows that there is a significant influence between motivation and employee performance. Hypothesis Test Results (F Test) Simultaneously Physical Work Environment (X1) and Motivation (X2) on Employee Performance (Y) Based on the research results, the calculated F value > F table or (47.400 > 3.17), this is also confirmed by significance value < 0.050 or (0.001 < 0.050). Thus, H03 is rejected and Ha3 is accepted, this shows that there is a significant simultaneous influence between the physical work environment and motivation on employee performance.